Evaluating the Immunogenicity of an Intranasal Microparticle Combination Vaccine for COVID-19 and Influenza - Sharon Vijayanand; Smital Patil; Priyal Bagwe; Revanth Singh; Emmanuel Adediran; Martin J. D’Souza (Vaccines)
Background: Infectious respiratory pathogens like SARS-CoV-2 and influenza frequently mutate, leading to the emergence of variants. This necessitates continuous updates to FDA-approved vaccines with booster shots targeting the circulating variants. Vaccine hesitancy and needle injections create inconvenience and contribute to reduced global vaccination rates. To address the burden of frequent painful injections, this manuscript explores the potential of non-invasive intranasal (IN) vaccine administration as an effective alternative to intramuscular (IM) shots. Further, as a proof-of-concept, an inactivated combination vaccine for COVID-19 and influenza was tested to eliminate the need for separate vaccinations. Methods: The methods involved encapsulating antigens and adjuvants in poly(lactic-co-glycolic acid) (PLGA) polymer matrices, achieving over 85% entrapment. The vaccine was evaluated in vitro for cytotoxicity and immunogenicity before being administered to 6–8-week-old Swiss Webster mice at weeks 0, 3, and 6. The mice were then assessed for antibody levels and cellular responses. Results: The intranasal microparticle (IN-MP) vaccine induced an innate immune response, autophagy, and were non-cytotoxic in vitro. In vivo, the vaccine led to high levels of virus-specific serum IgM, IgG, and IgA binding antibodies, as well as elevated IgG and IgA levels in the lung wash samples. The antibodies generated demonstrated neutralizing activity against the SARS-CoV-2 pseudovirus. Furthermore, the IN-MP vaccine prompted increased antigen-specific CD4+ and CD8+ T-cell responses in the vaccinated mice. Conclusions: The IN-MP combination vaccine produced immune responses comparable to or higher than the IM route, indicating its potential as an alternative to IM injections.